2010
DOI: 10.1111/j.1469-8986.2009.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of attentional bias in anxiety: Emotion and gender specificity

Abstract: Anxiety is characterized by cognitive biases, including attentional bias to emotional (especially threatening) stimuli. Accounts differ on the time course of attention to threat, but the literature generally confounds emotional valence and arousal and overlooks gender effects, both addressed in the present study. Nonpatients high in self-reported anxious apprehension, anxious arousal, or neither completed an emotion-word Stroop task during ERP recording. Hypotheses differentiated time course of preferential at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
178
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 115 publications
(156 reference statements)
16
178
2
Order By: Relevance
“…Generally these non-clinical studies did not find RT interference Li, et al, 2007;Sass, et al, 2010;Taake, et al, 2009;Thomas, et al, 2007), although it was induced in limited conditions in two studies (Taake, et al, 2009;van Hooff, et al, 2008).…”
Section: Non-clinical Erp Studies Of Emotional Stroop Tasksmentioning
confidence: 88%
See 1 more Smart Citation
“…Generally these non-clinical studies did not find RT interference Li, et al, 2007;Sass, et al, 2010;Taake, et al, 2009;Thomas, et al, 2007), although it was induced in limited conditions in two studies (Taake, et al, 2009;van Hooff, et al, 2008).…”
Section: Non-clinical Erp Studies Of Emotional Stroop Tasksmentioning
confidence: 88%
“…No consistent patterns emerged for N1, P2 or N2. Many studies found higher P3, LPPs (Li, et al, 2007;Sass, et al, 2010;Taake, Jaspers-Fayer, & Liotti, 2009;Thomas, et al, 2007), to negative versus netural stimuli.…”
Section: Non-clinical Erp Studies Of Emotional Stroop Tasksmentioning
confidence: 99%
“…Deliberate strategic and elaborative processes are thought to be mechanisms that arise later in attentional processing in order to counteract automatic biased processing of threat (Mathews and MacLeod 1994;Mogg and Bradley 1998;Yiend 2010), also leading to interference with ongoing task demands. Some evidence from research using the dot-probe paradigm in patients with anxiety has suggested that automatic allocation of attentional resources towards threat could potentially enhance an anxious state, which could further increase the dwell time on the threatening stimulus and thereby delay disengagement and facilitation of threat-congruent probe detection (Fox et al 2001;Ohman et al 2001;Cisler et al 2009); however there is further evidence suggesting that avoidance may also occur before there is conscious awareness, at the perceptual level, and immediately following threat detection (Mogg and Bradley 1998;Mauss et al 2007;Sass et al 2010;Huijding et al 2011). Such evidence is further supported by electrophysiological event-related potential (ERP) research, visual perception, and eye-tracking studies that have all indicated that shifting patterns of attention towards threatening stimuli may occur on the order of milliseconds and a time-course for avoidance of emotional stimuli can be described at the non-conscious level paralleling early activation of brain areas associated with threat detection (Bannerman et al 2010a, b;Koivisto and Revonsuo 2010;Railo et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Non-patients with increased levels of self-reported anxiety also display higher emotional bias towards emotionally valent words. (Tulen et al, 1989;Williams et al, 1996;Leite et al, 1999;Becker et al, 2001;Sass et al, 2010) Dot probe task Subjects are presented a combination of emotional and neutral facial expressions, and are asked to identify a dot sometimes presented in combination. Startle response to is measured both at baseline levels and subsequent to expose to the CS.…”
Section: Self-reporting Of Panic Response Alterations In Cardiac Funmentioning
confidence: 99%